Intravenous Magnesium for Chronic Complex Regional Pain Syndrome Type 1 (CRPS‐1). Issue 9 (25th July 2013) - Fischer, Sigrid G. L.; Collins, Susan; Boogaard, Sabine; Loer, Stephan A.; Zuurmond, Wouter W. A.; Perez, Roberto S. G. M.
Abstract Objective To assess the effects of intravenous administration of magnesium on complex regional pain syndrome type 1 (CRPS‐1), a randomized double‐blind placebo‐controlled trial was performed. Methods Fifty‐six patients with CRPS‐1 (International Association for the Study of Pain Orlando criteria) received MgSO4 70 mg/kg or placebo (NaCl 0.9%) in 4 hours over 5 consecutive days. Pain (BOX‐11 and McGill), the level of impairment (Impairment level Sum Score [ISS]), functional limitations (Radboud Skills Questionnaire, Walking Skills Questionnaire/questionnaire rising and sitting down), participation (Impact on Participation and Autonomy [IPA]), and quality of life (Short Form‐36, EuroQol, IPA) were evaluated at baseline and at 1, 3, 6, and 12 weeks. Results No significant differences were found between MgSO4 and placebo on the BOX‐11 and ISS at different time points during the trial on intention‐to‐treat and per‐protocol analysis. A significant improvement on the BOX‐11 was found after the first week of the trial in both groups (mean 0.7; standard deviation 1.1). For the MgSO4 group, a clinically relevant and statistically significant improvement on the ISS at 1 week (median 5, interquartile range [IQR] –1 to 8) and a significant improvement on the McGill up to 6 weeks (median 2 words, IQR 0–4.5) were found compared with baseline, which were not found in the placebo group. Significant improvement in perceived job participation was found for the MgSO4 group at 12 weeks (median improvement 1.44–1.17; P = 0.01). ISS improved significantly more in patients with a low Hospital Anxiety and Depression Scale (HADS) score (≤10) in the MgSO4 group (mean 4.4 vs mean −3.1; P = 0.02). Conclusion Administration of the physiological competitive N‐methyl‐D‐aspartate receptor antagonist magnesium in chronic CRPS provides insufficient benefit over placebo. Future research should focus on patients with acute CRPS and early signs and symptoms of central sensitization.